A pharmacist's role in increasing access to menstrual products: an education and advocacy approach - Potter, Kristal; Beal-Stahl, Jessica (Frontiers in Reproductive Health, 2024)
Individuals who menstruate grapple with diverse challenges in menstrual and reproductive health. This includes financial burdens, societal stigmas, and negative mental and physical health implications. Period poverty, marked by insufficient access to menstrual products, education, and sanitation, remains a prevalent and poorly addressed issue. Alarming statistics highlight the extent of this problem and shed light on the staggering number of individuals lacking access to essential menstrual products. The discourse extends to the safety and accessibility of a diverse array of menstrual products. A comprehensive comparison of the cost of available period products was conducted using data obtained from various retail websites. The often-overlooked potential indirect expenses and profound impacts on quality of life were also discussed. Amidst other public health initiatives, pharmacists have emerged as pivotal advocates and educators. Pharmacists are poised to drive initiatives that increase access to menstrual products through public health education and advocacy. By providing education on different menstrual product options, pharmacists can empower individuals to make informed decisions based on their needs. This perspective illuminates the complex impacts of menstruation on individuals and proposes that pharmacists can play a role in overcoming barriers to access. The proposed strategies, rooted in education, research, and advocacy, pave the way for enhancing access, reducing stigma, and elevating the quality of life for those navigating the intricate complexities of menstruation.